Risk Factors for Recurrent Thrombosis in Patients with Antiphospholipid Syndrome—A Single-Centre Cohort Study - Karandyszowska, Natali; Faustini, Francesca; Alagündüz, Hevgin; Widaeus, Jacob; Carlens, Felicia; Jensen, Ann-Louise; Oksanen, Anna; Magnusson, Maria; Gunnarsson, Iva; Svenungsson, Elisabet; Antovic, Aleksandra; Bruzelius, Maria (TH Open, 2025)
Recurrent thrombosis poses a clinical challenge in patients with antiphospholipid syndrome (APS). There are limited data on risk factors due to its rarity.This study aimed to study the association between cardiovascular (CV) and APS-related risk factors and recurrent thrombosis and evaluate the adjusted Global Anti-Phospholipid Syndrome Score (aGAPSS).This retrospective cohort study comprised APS patients at Karolinska University Hospital, Sweden, from 2014 to 2020 with follow-up until the last medical visit or death. Multiple thrombotic events per patient were included. Cox proportional hazard model estimated hazard ratios (HRs) and 95% confidence intervals (CIs). Logistic regression and Poisson regression were conducted to further examine the relation between risk factors and recurrent thrombosis.The cohort included 250 patients (67% women and 62% primary APS) with a median age of 44.5 (35–59) years. Forty-nine recurrent thrombotic events occurred in 36 patients, yielding an incidence of 4.46 (95% CI 3.30–5.90) per 100 person-years. Thrombocytopenia was associated with recurrent thrombosis (HR 2.57 [95% CI 1.01–6.02]). Although CV risk factors were not consistently significant for recurrent thrombosis, chronic kidney disease (CKD) indicated an increased probability (OR 2.55 [95% CI 1.01–6.26]). For each point of aGAPSS, the HR for recurrent thrombosis increased by 10% (1.10 [95% CI 1.01–1.19]). Notably, inadequate anticoagulation triggered recurrence in almost a quarter of cases.Thrombocytopenia was confirmed as a major risk factor for recurrent thrombosis. CKD warrants closer attention in future assessment. Although an increase in aGAPSS was associated with recurrent thrombosis, further evaluation is required. Improving anticoagulation treatment is essential to reduce recurrence.
Keywords: aGAPSS; antiphospholipid syndrome; recurrent thrombosis; risk factors; thrombocytopenia